Influence of the solvent in the synthesis of zeolitic imidazolate framework-8 (ZIF-8) nanocrystals at room temperature - Bustamante, Eugenia L. (2014)
The effect of the solvent on the synthesis process and on the nanocrystal characteristics of the zeolitic imidazolate framework-8 (ZIF-8) was investigated. A synthesis protocol at room temperature employing a series of aliphatic alcohols, water, dimethylformamide and acetone was employed. The results show that the solvent modifies the evolution of the reaction, altering the crystallization rates and nanocrystal sizes. Its hydrogen bond donation ability is the main factor that governs this effect. More precisely, the solvent modulates the formation of ZIF-8 nanocrystals with sizes in the range between 15 and 42 nm. When synthesized in alcohol and acetone, these nanocrystals form globular aggregates with sizes between 130 and 420 nm. In contrast, under the same synthesis conditions, when using water or dimethylformamide the ZIF phase is not developed. In alcohols other than methanol, the crystals develop pill-shaped morphologies with poorly defined facets. Moreover, a markedly fast growing kinetics is verified in these alcohols, leading to an ultra-fast crystallization of ZIF-8 in about 60 s. These findings provide new information about the role of the solvent in the synthesis process of nanoZIF-8, which can be useful for controlling the crystallization rates and nanocrystal sizes of this material.